Use of Medicinal Plants in Grogol Village Community as an Alternative Treatment for Illnesses - Sylvia, Dina; Husain, Fadly (Al-Hayat: Journal of Biology and Applied Biology, 2024)
Medicinal plants have been an important part of cultural heritage and community knowledge for generations. This study aims to determine the use of medicinal plants in urban environments, especially in Grogol Selatan Urban Village, South Jakarta. This research uses a descriptive qualitative approach by collecting data based on field observations in accordance with the object of research, interviews, and documentation. The results showed that there are still many people in Grogol slot thailand Selatan Village who believe in traditional medicine and utilize various types of medicinal plants, such as Abrus precatorius, Clitoria ternatea, and Morinda citrifolia, to treat various diseases. The utilization of these medicinal plants is a motivating factor for the community to get used to the use of natural materials "back to nature". People's perceptions of the use of medicinal plants are inherited from previous generations and are based on their personal experiences and knowledge. Plants that are still utilized by urban communities in Grogol Selatan Urban Village, South Jakarta such as Abrus precatorius as a cough medicine, internal heat, and fever. Clitoria ternatea as a medicine for eye pain, eye wash, and diabetes. Morinda citrifolia as a medicine for gout, hypertension, cholesterol, heat reduction, rheumatism, hair loss, and flatulence in infants. The parts of medicinal plants that are utilized are leaves, fruits, and flowers. These plant parts are very easy to utilize by soaking, boiling, chewing, pounding, squeezing, kneading, and mashing.